The Theatre of Photography: an interdisciplinary duologue - Anderson, Joel; Leister, Wiebke (Sens public, 2019)
Taking as a starting point the opposition of our title: this text, in the form of a duologue, is also a meeting between photography and theatre, a vantage point from which certain conceptual frameworks can be challenged and even collapsed. In the domain of theatre, one hears often of artifice, authenticity, likeness and liveness. Theatre, from the conceptualisation of naturalism in the nineteenth century to the challenges posed by performance art in the twentieth century, struggles with media (despite the eclecticism of its own technological apparatus), sometimes seeking distance from them. Photography studies, meanwhile, has often emphasised the possibility or impossibility of veracity, the truthfulness or deceptiveness of photographs, with performance seemingly offering one escape route… This duologue seeks only to cast light on certain crossings inside the theatre of photography, envisaging future dialogues between media and across disciplines.